Frost-Resistant Epoxy-Urethane Binders Containing Diglycidyl Urethane - Vladimir N. Strel’nikov; Valeriy Yu. Senichev; Alexey I. Slobodinyuk; Anna V. Savchuk; Elena R. Volkova (International Journal of Polymer Science)
A novel method for developing frost-resistant epoxy-urethane binders is proposed that is based on mixtures of epoxy-urethane oligomers and diglycidyl urethane formed during synthesis. The microheterogeneous elastic materials obtained by curing these mixtures by the cycloaliphatic amines have a low glass transition temperature and high mechanical properties.